The Tampat at Tuguis oral history among the Sangil of Sarangani - Gloria, Heidi K. (2008)
The southernmost province in the island of Mindanao is Sarangani, which is also the name of the bay that separates the provincial domain into an eastern and western part. Two small islands fronting the bay likewise used to be known as Sarangani. These islands were prominently cited in the chronicles of the Villalobos expedition, which was marooned in the bigger of the two islands. Villalobos and his men lived for about a month in the western part of the Sarangani Bay until they were forced to abandon the temporary settlement by hostile inhabitants. One of the oldest inhabitants of the area is the Sangil (Sangir, Sangirese) whose original homeland is the tiny archipelago of Sangihe Talaud in Indonesia. Communities of Sangil peoples have lived on both sides of the present Sarangani province for more than 600 years. They fought in the Moro Wars (16th-19th centuries) alongside the Magindanaos, Tausugs, Ternatans, and Caragans, with whom they were related. Today, they are a little known group living in remote communities in Sarangani Province. In reconstructing the history of Sarangani, one is obliged to address and acknowledge the Sangil. This paper focuses on the tampat (shrine) at Tuguis, in the present municipality of Kiamba, Sarangani, for it is there that an important institution among the Sarangani, for it is there that an important institution among the Sangil is found. The tampat at Tuguis is revered by the Sangil on both sided of Sarangani Bay. The guardians of this shrine claim to be direct descendants of the holy man whose remains are buried in the tomb. Methods of oral history were used, together with documentary sources, to resuscitate the historic past of the Sangil and the role they played in the history of Sarangani.
Includes bibliographical references (page 68).